Ефективна боротьба з корозією металів екологічно чистими засобами - Савенко, В. І.; Фіалко, Н. М.; Абделхамід ХаілАбуСал, Аднан; Висоцька, Л. М. (Ways to Improve Construction Efficiency, 2014)
Corrosion leads to millions of dollars losses every year, because corrosion (rust) puts out of action cars and products from metal. Protection and updatingof metal products demands additional expenses also. Research of processes of corrosion gives the qround to claim, that reliable protection against corrosion is: first of all – correct preparation of a surface, and afterthat, quality layer of sealants, paints or other types of covering. Environmentally friendly substance of phytogenesis is patended and tested under the name «CONTRAST».This substance is an effective remedy of blocking of sources of corrosion (rust),This substance is very good for preparation of surfacesfor sheetings also.